The Dynamics of State-Owned Assets Insurance Regulation Drafting from Regulation Theory Lens - Fakhri Nurfaiz; Taufik Raharjo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
State-owned assets (BMN) insurance is regulated by Minister of Finance Regulation (PMK) number 97 of 2019 which was issued as a replacement for PMK number 247 of 2016 for the reason of not successfully implemented as expected. Significant changes have occurred regarding BMN insurance through the 2019 PMK. The changes of regulation require strong urgency and arguments to be actualized. The arguments and discussions regarding regulation drafting come from many sources, from the regulator itself and the regulated parties. This research was conducted in the form of a case study to explore and get further understanding of the BMN insurance regulation drafting dynamics while observing through a regulation theory lens. The results of the study found that initially, the regulation drafting regarding BMN insurance was a necessity to have insurance as a risk transfer scheme, and also along the way, an intervention was needed for the failure of previous regulations while the assumed private motives involved coincide the public needs. The results also found that during the drafting process, there happened to be a capture process from the regulated party’s side to the regulator, but later explained that what was expected by the regulated parties was also expected by regulators.